Penerapan Algoritma C4.5 Untuk Klasifikasi Keterlambatan Pembayaran Premi Asuransi - Jefry Antonius Karlia; Wawan Nurmansyah (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2021)
The problem that often arises in insurance companies is the number of customers who do not smoothly pay premiums. The procedure that applies to the insurance during the grace period is 30 days. The insured customer must follow the premium payment procedure, if the customer does not pay the premium, the insurance policy will be canceled, this is part of the company's loss. An insurance company has a lot of data and this data can be processed to produce information on how to find out potential customer delays from a pattern formed using the C4.5 method. This research was conducted by applying the C4.5 algorithm using insurance customer data. The results of this study are a classification system for late payment of insurance premiums that can classify insurance customer premium payment status as a consideration for accepting insurance customers. The system test results show that the system can classify the status of insurance customer premium payments with a classification accuracy of 88%. Keywords: Algorithm C 4.5, Insurance, Classification, Premium